Social responsibility and consensus orientation in public governance - Tomaževič, Nina (Central European Public Administration Review, 2019)
Over the past two decades, social responsibility (SR) has become a key principle of many private sector entities that aim for business excel-lence. Similarly, in the public sector, the latest public governance mod-els (PGMs) are based on the selected public governance principles (e.g. consensus orientation, participation, equity and inclusiveness) directed at connecting and including all types of stakeholders in decision-making and carrying out the activities of public sector organisations. Yet, there is insufficient reliable empirical evidence with respect to the relationship between social responsibility and the underlying principles of PGMs. The principal goal of the article is thus to identify the relationship between the concept of social responsibility and consensus orientation, which is one of the main theoretically and practically grounded principles of PGMs. This goal is addressed by applying the QDA Miner software pack-age and analysing the contents of the 100 most relevant scientific papers from the Web of Science database. Specifically, the relationship between occurrence of the "consensus orientation" principle and SR is identified and quantified, revealing the importance of the latter. Moreover, differ-ent PGMs are analysed in terms of consensus orientation and SR enforce-ment, providing tangible guidelines to help advance theory and practice in the domain of public governance.
Keywords: consensus orientation; content analysis; governance models; literature review; public sector; social responsibility